Educational Tourism Activity Plan - Rahayu, Mia; Gunawan, Indra; Munir, Bintang Aditya Wardhana Putra; muchlis, Nur farah fajriaty; A. Bakty, Andi Fatimah Maoudy (Journal La Sociale, 2026)
Fort Rotterdam is one of the most important historical heritage sites of Makassar and has great opportunities in terms of development as an educational tourism destination. Even though the site has a good level of architectural integrity and cultural relevancy, the education functionality of the site is underused. The current research aims at evaluating current tourism conditions, the experience of visitors in the learning process, and the perspective of institutions in order to come up with proper and sustainability designs of educational tourism activities. The study uses a qualitative descriptive research approach. The information was collected by direct observation, semi-structured interviews with the visitors and site managers, and documentary materials. The observation was based on physical conditions, interpretive facilities and patterns of visitor activity. The perceptions, learning difficulties, expectations, and managerial constraints were investigated during interviews. The data obtained were categorised thematically and analysed through interpretation, the aim of which was to outline salient patterns and relationships. The findings indicate that Fort Rotterdam is physically in good condition and well-decorated, but the education systems and interpretation media are not many and are too scattered. Tourists use the site mainly in the recreational context, and their understanding of the historical accounts is still incomprehensible. However, interactive, culturally based and participatory learning activities are highly viewed by the majority of visitors. The site managers too demonstrate a dedication to education enhancement but they face limitations of human resource and financial aid. Considering these results, the paper suggests working on interactive educational programmes, including puzzle activities based on Lontara and digital interpretation tools and community-related learning programs. The strategies are expected to support visitor interaction, increased historical awareness and sustainable heritage tourism development at Fort Rotterdam.